Psychosocial distress among oncology patients in the safety net. Issue 11 (28th September 2020) - Cimino, Theora; Said, Kiana; Safier, Leslie; Harris, Heather; Kinderman, Anne
Abstract: Objective: Psychosocial distress among cancer patients leads to poor health outcomes and lower satisfaction. However, little is known about psychosocial distress among disadvantaged populations. We examined the prevalence, predictors, and follow‐up experience of psychosocial distress among cancer patients within a diverse, urban, and multi‐lingual safety‐net setting. Methods: We conducted a retrospective cohort study of cancer patients undergoing psychosocial distress screening at initial medical oncology visits from 2014‐2016. The primary outcome was self‐reported moderate to severe psychosocial distress, defined by the NCCN as a Distress Thermometer score ≥ 4. Predictors of distress were assessed using logistic regression. Patients reporting distress were contacted by telephone 1‐12 months later to reassess distress and assess completion of supportive service referrals. Results: Among 200 screened patients, 61% had moderate to severe psychosocial distress. African‐American race, psychiatric illness, greater number of emotional problems, and reported problems with housing, money, worry, sleep, memory or homelessness were associated with psychosocial distress. Among 39 patients with moderate to severe psychosocial distress who completed follow‐up (42% of eligible patients), mean distress scores decreased from 6.5 at screening to 4.5 at follow‐up ( P < .02). 56% of the supportive service referrals made at the initial visit were not completed. Conclusions: Cancer patients in the safety‐net experience more psychosocial distress than other populations, with persistently elevated distress levels and difficulty accessing supportive services. We identified subgroups that may be at higher risk for psychosocial distress. Closer follow‐up and assistance for patients who report high distress levels may be needed.